2011
DOI: 10.1111/j.1532-7078.2010.00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Picture Perception in Infants: Generalization From Two-Dimensional to Three-Dimensional Displays

Abstract: Two experiments investigated 9-month-old infants' abilities to recognize the correspondence between an actual three-dimensional (3D) object and its twodimensional (2D) representation, looking specifically at representations that did not literally depict the actual object: schematic line drawings. In Experiment 1, infants habituated to a line drawing of either a doll or a sheep and were then tested with the actual objects themselves. Infants habituated to the sheep drawing recovered to the unfamiliar but not th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
15
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 68 publications
3
15
0
1
Order By: Relevance
“…In one condition, we tested object recognition by keeping both objects visible. We predicted infants would reach more for the distractor, in keeping with findings from visual recognition memory studies (e.g., Jowkar‐Baniani & Schmuckler, ). A novelty preference with visible objects would suggest infants identify the target object as familiar from their exposure to its photograph, and are less interested in exploring it than the unfamiliar distractor object.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…In one condition, we tested object recognition by keeping both objects visible. We predicted infants would reach more for the distractor, in keeping with findings from visual recognition memory studies (e.g., Jowkar‐Baniani & Schmuckler, ). A novelty preference with visible objects would suggest infants identify the target object as familiar from their exposure to its photograph, and are less interested in exploring it than the unfamiliar distractor object.…”
supporting
confidence: 62%
“…Even then, toddlers are more likely to demonstrate transfer with increasing age and with more iconic pictures (e.g., Ganea et al, 2008;Simcock & DeLoache, 2006). To date, only one study has shown transfer from pictures to objects in the 1st year of life, using visual habituation with 9-montholds (Jowkar-Baniani & Schmuckler, 2011). However, those infants were less likely to show visual recognition memory in the picture-to-object condition than the object-to-picture condition, consistent with the literature suggesting that representations constructed from pictures are weaker than those constructed from objects (e.g., Carver et al, 2006;Mash & Bornstein, 2012).…”
Section: Discussionmentioning
confidence: 99%
“… There is reasonable evidence that 2D representations of events (video stimuli) are comparable with actual, live, real‐life 3D events with regard to infants’ perception of their content (Johnson & Náñez, 1995; Jowkar‐Baniani & Schmuckler, 2011). The role of interposition and perspective indices in a 2D adaptation of the drawbridge experiment was explicitly investigated by Durand and Lécuyer (2002), who were able to replicate findings obtained from “live” stimuli such as used by Baillargeon et al.…”
mentioning
confidence: 99%
“…Prior studies demonstrated that 9-month-olds can differentiate between depicted (2D) and real (3D) objects, and they typically reach for the actual 3D display when given a choice to do so (DeLoache, Pierroutsakos, Uttal, Rosengren, & Gottlieb, 1998;DeLoache, Strauss, & Maynard, 1979). Infants in this age group also appear to recognize the correspondence between 2D and 3D displays that confirms picture-to-object transfer across displays of the same or highly similar objects (Jowkar-Baniani & Schmuckler, 2011;Shinskey & Jachens, 2014).…”
mentioning
confidence: 66%